2014
DOI: 10.1186/1471-2407-14-614
|View full text |Cite
|
Sign up to set email alerts
|

Vasculotide, an Angiopoietin-1 mimetic, reduces acute skin ionizing radiation damage in a preclinical mouse model

Abstract: BackgroundMost cancer patients are treated with radiotherapy, but the treatment can also damage the surrounding normal tissue. Acute skin damage from cancer radiotherapy diminishes patients’ quality of life, yet effective biological interventions for this damage are lacking. Protecting microvascular endothelial cells from irradiation-induced perturbations is emerging as a targeted damage-reduction strategy. Since Angiopoetin-1 signaling through the Tie2 receptor on endothelial cells opposes microvascular pertu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 92 publications
2
23
0
Order By: Relevance
“…To minimize this limitation, a 5 point quadrant scan that captures the overall irradiated volume was employed. Despite the lack of spatial resolution, previous work in mice 5 has shown the ability of optical biomarkers averaged over a sparse area to differentiate not only irradiated and non-irradiated skin but also the impact of skin sparing interventional drugs such as Vasculotide 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize this limitation, a 5 point quadrant scan that captures the overall irradiated volume was employed. Despite the lack of spatial resolution, previous work in mice 5 has shown the ability of optical biomarkers averaged over a sparse area to differentiate not only irradiated and non-irradiated skin but also the impact of skin sparing interventional drugs such as Vasculotide 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood hemoglobin (Hb), tissue oxygen saturation (StO 2 ) or oxygenated hemoglobin (oxyHb) levels have been used as proxies for irradiation-induced erythema in mice [3][4][5][6] . Following irradiation, total Hb levels undergo fluctuations, but oxyHb or StO 2 undergo a characteristic early sharp rise, followed by a fall and another more persistent rise 3,6 . When irritants are used to induce skin erythema, vascular oxyHb levels directly correlate with the severity of the local erythema and inflammation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…75 Vasculotide also improved murine acute radiation skin damage, reducing inflammation and increasing endothelial cell density and survival. 76 Thus, studies focused on restoring the balance in the Tie2 signaling axis show beneficial effects for the treatment of diabetic wound healing and beyond.…”
Section: Patterns [Damps]mentioning
confidence: 99%
“…The total dose of 43 Gy was fractionated into 20 doses, beginning with milder doses, following the model of radiotherapy for cancer patients, and especially focusing on the sensitive case of breast cancer. Except the very specific type of athymic nude mice, previous studies reported the use of different types of hairy mice, such as C3n/HeN, BALB/c, and C57BLJ6, irradiating their flanks or hind legs by a single dose, such as 11, 15, 22, 30, 35, 44, 50, or 200 Gy [32, 39-43]. Using hairless mice, there is no need to shave the irradiated area, a factor which facilitates the repeated topical applications.…”
Section: Discussionmentioning
confidence: 99%